Vitamin D metabolism in acute and chronic cholestasis. Issue 10 (October 1979) - Jung, R. T.; Davie, M.; Siklos, P.; Chalmers, T. M.; Hunter, J. O.; Lawson, D. E. M.
Abstract : To study the effects of acute and chronic cholestasis on vitamin D metabolism we investigated six cases of acute extrahepatic obstructive jaundice and eight cases of primary biliary cirrhosis (PBC) (three supplemented with vitamin D). Plasma 25-hydroxyvitamin D (25OHD) was low in the patients with PBC unsupplemented with vitamin D but normal in obstructive jaundice. None of the patients with PBC showed radiological or histological evidence of osteomalacia. In PBC, dietary intake of vitamin D was low but response to ultra-violet irradiation of the skin was normal even in those with a considerably raised serum bilirubin. Patients with PBC or obstructive jaundice had low levels of 25 hydroxyvitamin D binding protein which correlated with the serum albumin. The half-life of intravenously injected 3 H vitamin D3 ( 3 HD3 ) and the subsequent production of 3 H 25OHD were normal in all the patients with obstructive jaundice and in most with PBC. The two patients with PBC who produced less 3 H 25OHD than expected were receiving vitamin D supplements. The urinary tritium ( 3 H) excretion after the injection of 3 HD3 correlated with the serum bilirubin. After the injection of 3 H 25OHD3 the urinary excretion of 3 H was minimal and did not correlate with the serum bilirubin, suggesting that the radioactivity appearing in the urine after the 3 H vitamin D3 injection was associated with vitamin D metabolites other than 25OHD. Factors contributing to the low plasma 25OHD in primary biliary cirrhosis may be a low dietary intake of vitamin D, inadequate exposure to ultra-violet light, and a tendency to urinary wastage of vitamin D metabolites.